FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN E-WALLET LINKAJA DI WILAYAH DKI JAKARTA - Widiyastuti (2022)
The development of E-wallets is growing rapidly because it's increasingly being adopted by the community, especially when the Covid-19 condition hits, thus creating great opportunities for businesses engaged in the E-wallet industry. One of the players in the digital wallet industry is LinkAja, but there is a problem with the number of LinkAja users and a decrease in the number of users of their service. This study aims to determine, analyze, and prove whether perceptions of convenience, perceived benefits, and sales promotions have an effect on interest in using LinkAja's E-wallet. This study uses a quantitative approach with primary data sources. Respondents in this study were people who knew and have intention to use LinkAja e-wallet in the DKI Jakarta province with. took 100 samples by purposive sampling method. Data was collected by a questionnaire. The analytical technique used in this research is PLS. The results of this study are (1) Perception of convenience has an effect on buying interest, with the original sample value of 18,5%. (2) Perception of Benefits has an effect on buying interest, with the original sample value of 50%. (3) Sales Promotion has an effect on buying interest, with the original sample value of 29%. The Adjusted R-Square result of buying interest is 88,7%, indicating that the research model is very good in interpreting the perception of convenience, perceived benefits, and sales promotion which together contribute to buying interest using the LinkAja.